¿Materia de España ? Imaginarios nacionales y persistencia del estereotipo español en la cultura francesa (1898-1936) - Ferran Archilés Cardona (Amnis)
Between 1898 and 1936 (that is to say between the colonial disaster of the War of Cuba and the beginning of the Civil War) in French culture a stereotype of the Spanish was maintained, whose origins lie in the construction of the romantic myth in the 19th century. This article seeks to deepen in the maintenance of this stereotype and the political and cultural reasons that could explain it. Rather than outline the capacity of resistance of the stereotype per se, its aim is to analyze what kind of function this stereotype fulfilled. In this sense, the article points out that the stereotype of Spain as a country of eternal traits, orientalized and “passionate”, acted as a counterpoint to a positive image of France. The image of Spain was, therefore, a key element for the French national self-representation. It is no coincidence that this stereotype was especially relevant in the French reactionary and conservative thinking.